Constraining the Carnival: Aetonormativity in Health and Hygiene books for children (International Journal of Food and Nutritional Sciences, 2022)
Throughout history, the significant influence of stories and books on young children has been widely acknowledged. Many children’s books are designed to instil accepted social norms and promote the development of productive members of society. The subject of health and hygiene is a commonly discussed topic in children’s literature, and adults have long struggled to educate children about the transition from nature to culture. Stories remain a popular form of entertainment and learning for children, and adults often employ them as a suitable means of teaching children about essential knowledge related to health and hygiene. Most children’s books focus on the carnivalesque experiences of child characters and the lessons they learn from them. This paper seeks to analyze how the carnival experiences of child characters are restricted for the greater good, thereby imparting health and hygiene lessons to child readers who engage with the text. Through a review of selected books, this study aims to shed light on the theory of Aetonormativity in children’s literature and its implications for understanding health and hygiene education in children’s books.